An assembly of means for processing a pineapple or the like. - Shamsuddin, Rosnah (2009)
The present invention relates to an assembly of means (100) for processing pineapple fruit for small or medium scale. The present invention comprising a means for peeling and coring (101), Slicing(201), and dicing the pineapple (301). The blades of the present invention are detachable for easy maintance.